New Trends in General Surgery - Bautista Iturrizaga, Juan (2000)
Currently, with the advance of science, more and more basic disciplines are associated with surgery exerting some influence and giving rise to the concept of Medical-Surgical Science. Besides that, surgery has evolved in paralel with immunology (in the field of transplants), interventional radiology and diagnostic-therapeutic endoscopy. Indeed, many of changes in surgery, such as the use of new diagnostic tools, approaches with shorter incisions, and the colaboration -still in an evaluative periodof robots as surgeon's assistants, are consequences of these technological improvements. Hence, nowadays, scientific advances have permitted us evolve to the current apogee of minimally invasive endoscopic surgical techniques.